Religious-Ecocentrism Sustainability Accounting: Beyond Utopia towards Universe Sustainability - I Gusti Ayu Agung Omika Dewi (International Journal of Religious and Cultural Studies, 2021)
This article aims to construct a research methodology in the field of Sustainability Accounting (SA) which refers to the concept of deep ecology based on eco-centrism as well as a religious holistic based on universal values of religious teachings. The construction was carried out to "revive" SA through an ecosophical philosophy combined with the values of religious teachings, so that SA can rediscover its spirit, soul, or identity, which places the interests of all beings into one unity with self-interest. The construction results found a new methodology, namely Religious-Ecocentrism which can arouse human consciousness at the highest level beyond the Utopian method which views the implementation of SA as referring to ecological ethics based on infinite love for all God's creatures in order to realize universe sustainability